Between Unity and Division: The Ecumenical Movement in the Korean Church – History, Characteristics, and Prospects - SHIN, Jaeshik (Studia Universitatis Babes-Bolyai Theologia Reformata Transylvanica, 2026)
This article examines the ecumenical movement in the Korean church as a historically layered and socially embodied pursuit of Christian unity. Rather than defining unity only in terms of doctrinal agreement or institutional merger, the article approaches it as a comprehensive field of activity comprising historical development, theological discourse, institutional organization, and ritual practice. Such an approach is necessary because the Korean ecumenical movement has unfolded not simply as an intra-church theological project but as a dynamic response to the political and social crises of modern Korean history. Japanese colonialism, national division, the Korean War, authoritarian modernization, democratization, and contemporary polarization each shaped both the possibilities and the limitations of ecumenical engagement. The article therefore argues that the Korean ecumenical movement must be understood within the entangled history of Korean Christianity and Korean society. The study proceeds in four analytical stages. First, it traces the historical development of the movement from missionary coordination under colonial rule, through post-liberation reconstruction and denominational schism, to the public activism of the democratization era and the diversification and decline of recent decades. In this process, anti-communism, denominational division, and the growth of conservative Protestant organizations emerge as decisive forces that configured the split between ecumenical and anti-ecumenical camps. Second, the article considers the theological dimension of the movement. It shows that, despite the early adoption of broad confessional standards and the later reception of global ecumenical themes such as Missio Dei, Justice, Peace and the Integrity of Creation, and the Pilgrimage of Justice and Peace, Korean Protestantism has not produced a broadly shared modern confession of unity. Theological discussion has often remained confined to specialists and has rarely been translated into the ordinary life of congregations. Third, the article analyses the institutional dimension of Korean ecumenism. The National Council of Churches in Korea functioned for decades as the central organizational vehicle of the movement, linking churches, para-church agencies, and global ecumenical networks, yet its public role has weakened since democratization because of conservative Protestant mobilization, the transfer of activist energy to civil society, and declining international support. At the same time, newer forms of inter-church cooperation, including the Commission on Faith and Order of Korean Churches, suggest that ecumenical life in Korea has not disappeared but has changed its form and field of operation. Fourth, the article explores the ritual dimension of unity through World Communion Sunday, the Week of Prayer for Christian Unity, Easter joint services, and prayers for peace and reunification on the Korean Peninsula. These practices demonstrate that liturgical expressions of unity exist, but they also reveal the continuing distance between ecumenical leadership and congregational reception. On the basis of this analysis, the article argues that the Korean ecumenical movement has been historically influential but structurally fragile. It has been stronger as a movement for social witness than as a project of visible ecclesial convergence; stronger in national crises than in the patient cultivation of ordinary habits of inter-church trust; and stronger among elite leaders than among local congregations. The future of Korean ecumenism therefore depends on widening participation, renewing theological education, strengthening the role of women, younger Christians, and lay professionals, and recovering the ecclesiological, catechetical, and liturgical dimensions that were often overshadowed by activist urgency. The article concludes that Korean ecumenism still retains enduring significance, not because it has overcome division but because it continues to witness to the claim that the church cannot detach itself from the suffering, fragmentation, and common life of the nation.